2015
DOI: 10.17957/ijab/15.0028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dense Planting with Less Basal N Fertilization on Rice Yield, N Use Efficiency and Greenhouse Gas Emissions

Abstract: Rice cropping innovations for high yield with high N use efficiency (NUE) and low greenhouse gas (GHG) emissions are significant in ensuring food security and coping with climate change. The objective of this study was to investigate the comprehensive effects of dense planting with less basal N application (DR) on rice yield, NUE and GHG emissions. Field experiments were conducted at three sites in China: Shenyang, Danyang and Jinxian representing annual single rice cropping system, wheat-rice cropping system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…This experimental study showed that GHGs fluxes exhibited lower emissions at the D2 density level (Figures 3-5), indicating that appropriately increasing the alfalfa density is beneficial to reducing GHGs emissions in the jujube-alfalfa intercropping system. The CH4 emissions of the jujube-alfalfa intercropping system varied from −0.33 to 0.072 mg m −2 h −1 , and the appropriate alfalfa density exerted a certain deposition effect on the atmospheric CH4 uptake, which was similar to the results of the study on rice by Zhu Xiangcheng et al [32]. A large number of studies have shown that excessive nitrogen fertilizer inputs are the main factors contributing to GHG emissions from agricultural fields [13,33], and methods for optimizing the nitrogen inputs in cropping systems have become a primary issue in reducing GHs emissions from fields [34].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This experimental study showed that GHGs fluxes exhibited lower emissions at the D2 density level (Figures 3-5), indicating that appropriately increasing the alfalfa density is beneficial to reducing GHGs emissions in the jujube-alfalfa intercropping system. The CH4 emissions of the jujube-alfalfa intercropping system varied from −0.33 to 0.072 mg m −2 h −1 , and the appropriate alfalfa density exerted a certain deposition effect on the atmospheric CH4 uptake, which was similar to the results of the study on rice by Zhu Xiangcheng et al [32]. A large number of studies have shown that excessive nitrogen fertilizer inputs are the main factors contributing to GHG emissions from agricultural fields [13,33], and methods for optimizing the nitrogen inputs in cropping systems have become a primary issue in reducing GHs emissions from fields [34].…”
Section: Discussionsupporting
confidence: 85%
“…This experimental study showed that GHGs fluxes exhibited lower emissions at the D2 density level (Figures 3-5), indicating that appropriately increasing the alfalfa density is beneficial to reducing GHGs emissions in the jujube-alfalfa intercropping system. The CH 4 emissions of the jujube-alfalfa intercropping system varied from −0.33 to 0.072 mg m −2 h −1 , and the appropriate alfalfa density exerted a certain deposition effect on the atmospheric CH 4 uptake, which was similar to the results of the study on rice by Zhu Xiangcheng et al [32].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Plastic pots (diameter, 22 cm; height, 20 cm) were filled with 4.5 kg of air-dried soil. The diameter and height of the pots reflect common rice transplant density (25 cm × 15 cm per plant) and plow layer depth (0-15 cm) in paddy fields (Chu, Chen, Wang, Yang, & Zhang, 2014;Zhu et al, 2015). We transplanted two healthy rice seedlings into each pot, using six pots per treatment combination.…”
Section: Experiments A-cultivarsmentioning
confidence: 99%
“…Numerous studies have reported that reasonably dense planting was beneficial to improve rice yield associated with the increase of panicle number (Huang et al., 2013; Islam et al., 2013; Zhao et al., 2013). In addition, some studies found that increasing the planting density could compensate for the negative effect of reducing nitrogen rate on rice yield (Hou et al., 2019; Zhu et al., 2015). However, it is not clear whether increasing the planting density can alleviate the yield loss caused by prolonged seedling age.…”
Section: Introductionmentioning
confidence: 99%